Cholinergic Activation Enhances Resistance to Oral Salmonella Infection by Modulating Innate Immune Defense Mechanisms at the Intestinal Barrier - Al-Barazie, Ray M.; Bashir, Ghada Hassan; Qureshi, Mohammed M.; Mohamed, Yassir A.; Al-Sbiei, Ashraf; Tariq, Saeed; Lammers, Wim J.; al-Ramadi, Basel K.; Fernandez-Cabezudo, Maria J. (Frontiers in Immunology, 2018)
Inflammation is a crucial defense mechanism that protects the body from the devastating effects of invading pathogens. However, an unrestrained inflammatory reaction may result in systemic manifestations with dire consequences to the host. The extent of activation of the inflammatory response is tightly regulated through immunological and neural pathways. Previously, we demonstrated that cholinergic stimulation confers enhanced protection in experimental animals orally infected with virulent Salmonella enterica serovar Typhimurium. In this study, we investigated the mechanism by which this enhanced protection takes place. Cholinergic stimulation was induced by a 3-week pretreatment with paraoxon, a highly specific acetylcholinesterase inhibitor. This treatment enhanced host survival following oral-route infection and this correlated with significantly reduced bacterial load in systemic target organs. Enhanced protection was not due to increased gut motility or rapid bacterial clearance from the gastrointestinal tract. Moreover, protection against bacterial infection was not evident when the animals were infected systemically, suggesting that acetylcholine-mediated protective effect was mostly confined to the gut mucosal tissue. In vivo imaging demonstrated a more localized infection and delay in bacterial dissemination into systemic organs in mice pre-treated with paraoxon. Morphological analysis of the small intestine (ileum) showed that acetylcholinesterase inhibition induced the degranulation of goblet cells and Paneth cells, two specialized secretory cells involved in innate immunity. Our findings demonstrate a crucial pathway between neural and immune systems that acts at the mucosal interface to protect the host against oral pathogens.